An employment guarantee at risk insurance? Assessing the effects of the NREGS on agricultural production decisions - Esther Gehrke (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2014)
This paper assesses the role of risk constraints in households' production decisions. Using representative panel data for Andhra Pradesh, India, it analyses the effects of the National Rural Employment Guarantee Scheme (NREGS) on households' crop choices. This paper shows that the introduction of the NREGS reduces households' uncertainty about future income streams because it provides reliable employment opportunities in rural areas independently of weather shocks and crop failure. Households with access to the NREGS can therefore increase the share of inputs allocated to more profitable but also riskier crops, especially cotton. These shifts in agricultural production can considerably raise the incomes of smallholder farmers. Linking the employment guarantee to risk considerations is the key innovation of this paper. Therewith, it provides empirical evidence of the validity of the theory of decision-making under uncertainty and contributes to the ongoing debate on the effects of the NREGS on agricultural productivity.
Keywords: I38; O12; Q16; 330; Uncertainty; Employment Guarantee; Crop choice